Metasurface eyepiece for augmented reality - Gun-Yeal Lee (Nature Portfolio, 2018)
Here, the authors demonstrate a metasurface application to realize a compact near-eye display system for augmented reality with a wide field of view, full-color imaging, high resolution and a sufficiently large eyebox.